2015
DOI: 10.1097/nen.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Major Histocompatibility Complex Class I Upregulation and Restrictive Infection by JC Virus Hamper Detection of Neurons by T Lymphocytes in the Central Nervous System

Abstract: The human polyomavirus JC (JCV) infects glial cells in immunosuppressed individuals leading to progressive multifocal leukoencephalopathy (PML). JCV can also infect neurons in patients with JCV granule cell neuronopathy and JCV encephalopathy. CD8-positive T-cells play a crucial role in viral containment and outcome in PML but whether CD8-positive T-cells can also recognize JCV-infected neurons is unclear. We used immunohistochemistry to determine the prevalence of T-cells in neuron-rich areas of archival brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…Similarly, JCV-infected cerebellar granule cell neurons have been found in up to 79% of brains from people with PML 132 , and infected leptomeningeal cells have been found in 29% of brains from people with PML 146 . In these studies, infected neurons most commonly expressed T antigen but not VP1 capsid protein, suggesting abortive or restricted infection that may evade immune detection 147 .…”
Section: Iatrogenic Pmlmentioning
confidence: 87%
“…Similarly, JCV-infected cerebellar granule cell neurons have been found in up to 79% of brains from people with PML 132 , and infected leptomeningeal cells have been found in 29% of brains from people with PML 146 . In these studies, infected neurons most commonly expressed T antigen but not VP1 capsid protein, suggesting abortive or restricted infection that may evade immune detection 147 .…”
Section: Iatrogenic Pmlmentioning
confidence: 87%
“…However, if a virus gains access to the CNS, it is difficult to remove (Reinhold and Rittner, 2017). Due to the lack of major histocompatibility complex antigens in nerve cells, the elimination of viruses in nerve cells depends solely on the role of cytotoxic T cells; however, the apoptosis of mature neurons after virus infection also has a relatively protective effect (Wuthrich et al, 2015). Furthermore, the homeostasis characteristics of the cells in the CNS also contribute to the continued existence of the virus (Reinhold and Rittner, 2017) ( Fig.…”
Section: Othersmentioning
confidence: 99%
“…The responses of both types of T cell are triggered through T cell receptors (TCRs) that recognize small, processed peptides presented to them by major histocompatibility complex (MHC) molecules on antigen-presenting cells; peptide fragments bound to MHC molecules are known as MHC–peptide complexes. CD4 + T cells recognize antigens bound to MHC class II molecules present on the surface of antigen-presenting cells, including astrocytes and other glial cells 130,131 , and CD8 + T cells respond to antigens presented by MHC class I molecules, which are expressed on all nucleated cells but very rarely by neurons 132134 . A T cell is initially considered ‘naive’ before it encounters the antigen that binds its specific TCR.…”
Section: Evidence For An Autoimmune Mechanismmentioning
confidence: 99%
“…Using a transgenic mouse model in which orexin neurons expressed haemagglutinin and T cells possessed a TCR specific for haemagglutinin, one group showed that CD8 + T cells are capable of destroying orexin neurons 165 . However, a primary CD8 + cell attack on the orexin neurons is not likely to occur in NT1, as MHC class I molecules, which are involved in the activation of CD8 + T cells, are rarely expressed by neurons in humans, except very early in development and after exposure to interferon-γ 132134 .…”
Section: Evidence For An Autoimmune Mechanismmentioning
confidence: 99%